EIB Investment Report 2022/2023 Resilience and renewal in Europe - European Investment Bank (European Investment Bank, 2023)
Political strife caused by the war in Ukraine, an energy crisis and tightening credit are hitting EU firms just as they were beginning to emerge from the COVID-19 crisis. While the pandemic was a major shock, sizable policy support enabled firms to survive and transform. Relatively easy access to funding also helped them weather the crisis. Pandemic support has since been pulled back, however, and now firms are grappling with high inflation, instability and tighter credit conditions. These combined pressures are souring firms' outlook. The report provides insight into the state of the European economy and its ability to withstand these crises while also becoming greener and more digital. The analysis is based on the EIB Group's annual Investment Survey, which surveyed 13 000 firms in the European Union from April until July 2022 on their performance, investment, financing issues and challenges. The report's Key Findings are available here. Contents Executive summary Introduction Part I Investment environment in a time of crises 1. The macroeconomic context 2. Investment in Europe 3. A corporate sector buffeted by shocks Part II Resilience and renewal 4. Trends in regional and social cohesion 5. Progress on digital transformation 6. Green transition and the energy crisis Data annex Glossary of terms and acronyms The chapters in charts Chapter 1 - The macroeconomic context Chapter 2 - Investment in Europe Chapter 3 - A corporate sector buffeted by shocks Chapter 4 - Regional and social cohesion Chapter 5 - Progress on digital transformation Chapter 6 - The energy crisis and green transition